1988
DOI: 10.1136/bmj.296.6614.11
|View full text |Cite
|
Sign up to set email alerts
|

Acylcoenzyme A dehydrogenase deficiency in heart tissue from infants who died unexpectedly with fatty change in the liver

Abstract: Heart muscle from infants who died unexpectedly and who showed fatty changes in the liver at necropsy was analysed for long chain and medium chain acylcoenzyme A dehydrogenase activities by using the natural electron acceptor. In two of the seven cases investigated a deficiency in acylcoenzyme A dehydrogenase activity was found. In one case the deficiency was in medium chain acylcoenzyme A dehydrogenase activity and in the other long chain acylcoenzyme A dehydrogenase activity. These findings emphasise the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…We investigated this method by immunoblotting using anti-human VLCAD antibody. About 20 and 80% of VLCAD protein were distributed to the supernatant and membrane fractions, respectively, suggesting that it is possible to identify VLCAD deficiency by measuring palmitoyl-CoA dehydrogenation activity in membrane fraction; in contrast, it may be hard to identify isolated LCAD deficiency by measuring this activity in supernatant fraction containing significant amounts of contaminating VLCAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated this method by immunoblotting using anti-human VLCAD antibody. About 20 and 80% of VLCAD protein were distributed to the supernatant and membrane fractions, respectively, suggesting that it is possible to identify VLCAD deficiency by measuring palmitoyl-CoA dehydrogenation activity in membrane fraction; in contrast, it may be hard to identify isolated LCAD deficiency by measuring this activity in supernatant fraction containing significant amounts of contaminating VLCAD.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to MCAD deficiency, other defects, such as short-chain acyl-CoA dehydrogenase and long-chain acyl-CoA dehydrogenase (LCAD) deficiencies, are rare. The detailed clinical descriptions of these defects are quite variable, and many patients die before 1 yr of age (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Lanes 1 and 2, 100 and 10 ng, respectively, of purified rat MCAD were directly applied as standard; lanes 3 and 4, 133 ng of rat MCAD after preabsorption with preimmune rabbit serum and anti-LCAD antibody, respectively; lanes 5 and 6, 13.3 ng of rat MCAD after preabsorption with preimmune rabbit serum and anti-LCAD antibody, respectively. The intense bands above the MCAD bands (lanes [3][4][5][6] are the heavy chain of IgG derived from the preimmune serum or the antibodies used. The broad, faint bands seen in each lane are a result of BSA being used as a camer.…”
Section: Characterization Of Interactions Of Rat and Human L C A D Andmentioning
confidence: 99%
“…Heterogeneity of LCAD deficiency was also suggested by a biochemical assay (3). As in the case of MCAD deficiency (4), some patients with LCAD deficiency abruptly died with few prodromal symptoms, mimicking sudden infant death syndrome (5). No urinary metabolites are specific for this disease, making it difficult to establish the diagnosis.…”
mentioning
confidence: 99%
“…A retrospective study of material collected at autopsy from 200 consecutive sudden infant deaths identified 14 with severe diffuse microvesicular panlobular fatty infiltration of the liver. In nine cases sufficient stored material (liver or heart muscle) was available for specific enzyme assays, leading to the diagnosis of three cases of medium-chain and one of long-chain acyl-CoA dehydrogenase deficiency (Howat et al, 1985;Allison et al, 1988a). In two of the cases of medium-chain acyl-CoA dehydrogenase deficiency the diagnosis was confirmed by the subsequent birth of affected siblings while in the third case a small amount of urine, collected post-mortem, contained high concentrations of dicarboxylic acids as expected.…”
Section: Sudden Infant Deathmentioning
confidence: 99%